Creep of compression fly ash concrete-filled steel tubular members. (May 2017) - Han, Bing; Jiao, Yu-Ying; Xie, Hui-Bing; Zhu, Li
Abstract: Because of its rational mechanical performances, concrete-filled steel tubes (CFT) have been widely used in construction. To improve the reliability of CFT structures, steel tubes are filled with fly ash concrete (FAC) to increase the workability and compactness of the concrete core. Because the hydration process of concrete changes with the addition of fly ash, creep in fly ash concrete shows obvious differences compared with common concrete. As an important long-term behavior of CFT structures, creep has significant effects such as extra deflection, or stress redistribution between steel tube and concrete core. These effects become more complicated after using FAC, and studies of the effects are limited. In this study, the compressive levels of creep in plain FAC and fly ash concrete-filled steel tubes (FACFTs) were measured. The effects of the two fly ash-replacement ratios, 20% and 40%, on creep were investigated. On the basis of an inverse analysis method, a creep model of plain FAC was regressed according to the test data. After a linear stress–strain relationship of compressive FACFTs was established, the creep model was introduced to predict the creep of FACFTs. By comparing the predicted results and by testing the creep of FACFTs, this approach for predicting the creep of compressive FACFTs has shown desirable accuracy. The findings illustrate that fly ash has un-ignorable effects on the creep of FACFTs and that using a linear model to predict the creep of CFTs under low stress levels is feasible. Highlights: A series creep experiments of FAC and FACFT with two kinds of replacement ratio of fly ash were conducted. An approach based on the creep test data of plain FAC was proposed to predict the creep of FACFT. Influence of fly ash replacement ratio on creep of FACFT was revealed.